A clinical case of erythema multiforme associated with HSV 1/2 in a child - Frych , Sophia; Kys , Maryna; Korbut , Oksana (The Ukrainian Scientific Medical Youth Journal, 2023)
This research examines a clinical case of erythema multiforme in a 5-year-old child, which was triggered by HSV-1. Clinically, the child presented with a fever of 37.5–38.0°C, itching, and a papular-vesicular rash with ring-shaped hyperemia around the vesicles on the face, trunk, limbs, and edema. Instrumental and laboratory investigations did not reveal any abnormalities. The blood serum analysis detected positive Ab IgG HSV1/2 (qualitative method) with a value of 24.7 S/CO and a dubious result for Ab IgM HSV 1/2 , indicating the presence of a herpes infection. Considering the clinical, laboratory, and instrumental findings, a differential diagnosis was required to distinguish between erythema multiforme triggered by HSV-1 and chickenpox in order to prescribe the appropriate treatment and prevent complications.